2015
DOI: 10.2196/resprot.3806
|View full text |Cite
|
Sign up to set email alerts
|

Prescription Tablets in the Digital Age: A Cross-Sectional Study Exploring Patient and Physician Attitudes Toward the Use of Tablets for Clinic-Based Personalized Health Care Information Exchange

Abstract: BackgroundTo reduce the cost of health care while increasing efficiency and quality, health systems are seeking innovative means to engage and empower patients. Improved use of information technology and electronic health record (EHR) infrastructure is essential, and required for “meaningful use” as mandated by the federal government. Providing personalized health information using tablets at the point of care could enhance the clinical experience and enable efficient collection of patient reported outcome mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…Recently published studies confirm high potential of mobile apps delivered via tablet computers or smartphones for patient-centered hospital-based programs aimed at patient education, engagement, and empowerment [ 78 - 80 ]. Growing number of clinicians endorse use of tablets for personalized care delivery to their patients [ 81 ]. Employing more comprehensive computer-assisted interventions using a variety of behavioral constructs tailored to individual patient profiles over prolonged period of time may significantly enhance the performance of such systems in the future [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently published studies confirm high potential of mobile apps delivered via tablet computers or smartphones for patient-centered hospital-based programs aimed at patient education, engagement, and empowerment [ 78 - 80 ]. Growing number of clinicians endorse use of tablets for personalized care delivery to their patients [ 81 ]. Employing more comprehensive computer-assisted interventions using a variety of behavioral constructs tailored to individual patient profiles over prolonged period of time may significantly enhance the performance of such systems in the future [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given these challenges, our team sought to design a technology solution to facilitate visit communication between complex patients and their primary care providers. Mobile health tools like tablets offer a well-matched strategy for improving communication in a way that minimizes impact to the clinician workflow and better utilizes patients’ time in clinic [ 12 ]. Tablets in the waiting room are being increasingly used to (1) educate patients about specific health topics and (2) collect patient-reported outcome data to inform care [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…As READY creates a shared platform by integrating data from both patients and physicians, the influence of technology on physician and patient interactions may become either an obstacle or the enabler of physicians' use of technology [35]. One study reported that patients and physicians were highly amenable to integrating mobile devices into clinical settings, as they are useful in collecting patient-reported outcome measures and improving patient-provider communication [36]. Another study reported that some physicians shared com-puter screens to build trust with patients; On the other hand, several physicians also reported that it was time consuming and caused distractions [37].…”
Section: Shared Decision Making Using a Mobile App In Outpatient Settmentioning
confidence: 99%